TINGKAT KEPUASAN KONSUMEN TERHADAP PRODUK OLAHAN PERIKANANPEMPEK CV. XYZ DI SAMARINDA - Muhammad Syifa Habibi; Elly Purnamasari; Heru Susilo (Jurnal Pembangunan Perikanan dan Agribisnis, 2022)
Pempek is one of the foods favored by the people of Indonesia. This causes many people to process pempek and make it a business. The number of pempek processing businesses makes the competition higher, therefore a study was conducted on pempek CV. XYZ for 10 months from April 2021 to January 2022 to determine the level of customer satisfaction. This study aims to analyze the characteristics of the respondents, the level of consumer satisfaction, and any attributes of pempek CV. XYZ which needs to be improved. The sampling method used was both purposive sampling and accidental sampling by distributing questionnaires to 55 respondents. In addition, the census is also used to obtain business profile information by interviewing business owners. The data processing method used is descriptive analysis, Customer Satisfaction Index (CSI), and Importance Performance Analysis (IPA). Characteristics of respondents are dominated by women aged 21 - 25, unmarried with the latest high school education, working as a student, and having a monthly income of less than Rp. 500.000,-. The results of the CSI analysis showed the level of customer satisfaction is 69.07%, which means that consumers were satisfied with the performance of Pempek CV. XYZ. To increase the level of customer satisfaction further, it is necessary to improve the existing attributes. The results of the IPA analysis showed that the main priority for improvement so that customer satisfaction can increase, namely clarity of expiration date and clarity of composition.